The Lived Experiences of Manobo Tribe Living in Marginalized Community - Quiñones, Rocelyn; Marwisa S. Salam (Department of Public Administration, Parahyangan Catholic University, 2026)
This research explores the challenges faced by Manobo tribes in accessing social services and recognition within society. Through a qualitative approach using interviews, this study listens to people from a marginalized community in Barangay Ilomavis to understand their everyday lives. It highlights their struggles with social exclusion, securing a livelihood, managing finances, accessing sufficient food, and obtaining healthcare and education. The findings show that people are excluded from society in many ways. What keeps them disadvantaged is the combined effect of poverty, culture, and the place where they live. Even though government and non-government organizations try to help by offering services and aid, people still face ongoing difficulties in getting basic needs and opportunities. Beyond these challenges, the study shows that people want to improve their own lives and their community, especially through real improvements in roads, facilities, education, and healthcare. This study adds to the understanding of socio-economic realities faced by vulnerable communities and offers implications for policy makers, local government units, NGOs, and future researchers. Through these definitions, the study leverages on notions such as the Manobo Tribe and marginalized community and lived experience to further social justice discourse and equity in diverse contexts.